2012
DOI: 10.5194/bg-9-1611-2012
|View full text |Cite
|
Sign up to set email alerts
|

Are ammonia emissions from field-applied slurry substantially over-estimated in European emission inventories?

Abstract: Abstract. The EMEP/EEA guidebook 2009 for agricultural emission inventories reports an average ammonia (NH3) emission factor (EF) by volatilisation of 55% of the applied total ammoniacal nitrogen (TAN) content for cattle slurry, and 35% losses for pig slurry, irrespective of the type of surface or slurry characteristics such as dry matter content and pH. In this review article, we compiled over 350 measurements of EFs published between 1991 and 2011. The standard slurry application technique during the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 95 publications
5
67
2
Order By: Relevance
“…This is comparable with other models (Im et al, 2015). However, short periods with strong overestimations of [NO − 3 ] were also observed in previous New scheme (this study) 50 % * * Suggested by Sintermann et al (2012), Backes et al (2016), and Chen et al (2016b). studies. This seems to be the case for the HOPE Melpitz campaign simulation, during which COSMO-MUSCAT highly overpredicted [NO − 3 ] over Germany in this study (Fig.…”
Section: Improvement Of the Particulate Nitrate Predictionsupporting
confidence: 74%
See 1 more Smart Citation
“…This is comparable with other models (Im et al, 2015). However, short periods with strong overestimations of [NO − 3 ] were also observed in previous New scheme (this study) 50 % * * Suggested by Sintermann et al (2012), Backes et al (2016), and Chen et al (2016b). studies. This seems to be the case for the HOPE Melpitz campaign simulation, during which COSMO-MUSCAT highly overpredicted [NO − 3 ] over Germany in this study (Fig.…”
Section: Improvement Of the Particulate Nitrate Predictionsupporting
confidence: 74%
“…Note that EC and BC are usually interchangeable in modelling studies (Vignati et al, 2010;Chen et al, 2016a;Nordmann et al, 2014). The emission of NH 3 was reduced by 50 %, since over 90 % of NH 3 emissions in Europe are contributed by agricultural sources (Hertel et al, 2011;Erisman et al, 2008;Reidy et al, 2008), and agriculture emissions of NH 3 are overestimated by ∼ 50 % or even more (Sintermann et al, 2012;Backes et al, 2016). Also, Chen et al (2016b) adopted the same NH 3 emission inventory in the WRF-Chem model and reported that total NH 3 was overestimated by a factory of ∼ 2 at Melpitz during the campaign period.…”
Section: The Model System Cosmo-muscatmentioning
confidence: 99%
“…For field applied manures, the pH of cattle and pig slurries is typically in the range 7.5-8, but values down to 6.3 and up to 9.0 have been reported (Sintermann et al, 2012). This, combined with the natural variability of soil pH across agricultural landscapes in which manures are applied to land, contributes to the large variability in fluxes and NH 3 emission factors (EF) (Génermont and Cellier, 1997;Søgaard et al, 2002;Sommer et al, 2003;Sintermann et al, 2012).…”
Section: Surface/substrate Ph and Acid/base Ratiomentioning
confidence: 99%
“…This, combined with the natural variability of soil pH across agricultural landscapes in which manures are applied to land, contributes to the large variability in fluxes and NH 3 emission factors (EF) (Génermont and Cellier, 1997;Søgaard et al, 2002;Sommer et al, 2003;Sintermann et al, 2012). It should be noted that farmers typically monitor and manage soil pH to insure it is in an optimal range for the crop being produced and models should take this into account when estimating NH 3 fluxes for agricultural crops.…”
Section: Surface/substrate Ph and Acid/base Ratiomentioning
confidence: 99%
“…Dynamic chambers or movable wind tunnels may be used to estimate emissions from simulated grazing in the laboratory or the field ). However enclosure measurements may not always be representative of emissions at the field scale (Genermont and Cellier, 1997;Sintermann et al, 2012). The inverse dispersion method concerns the inferring of the atmospheric emission rate (Q) of localised gas sources from the excess concentration ( C) they cause above background, by modelling the C/Q relationship for a given source-receptor configuration and meteorological state (Flesch et al, 2004(Flesch et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%